Fabrication and characterization of MOCVD (In1-xAlx)2O3 (0.1≤x≤0.6) ternary films. Issue 2 (15th January 2022) - Li, Zhao; Xin, Yangmei; Xiu, Junshan; Liu, Yunyan; Yu, Dan; Liu, Huiqiang
Abstract: A series of (In1- x Al x )2 O3 (0.1 ≤ x ≤ 0.6) films with tunable bandgap were grown on MgO (100) substrates by MOCVD. The influences of chemical compositions and growth temperatures on the film properties were studied systematically. XRD analyses indicated that the film quality degraded from crystalline to amorphous structure as Al concentration ( x ) increased. The (In1- x Al x )2 O3 films prepared at 700 °C exhibited better film crystallinity than those of the ones grown at 600 °C. The films prepared at 700 °C with x = 0.1–0.3 showed an epitaxial In2 O3 <111> orientation with the corresponding growth relationship of In2 O3 (111)∥MgO (100). The film with x = 0.2 exhibited the best crystallinity and the largest grain size of 25.9 nm. The Hall mobilities and resistivities of the films were influenced evidently by Al concentrations. The Hall mobility showed a monotonous decrease from 12 to 1.1 cm 2 V −1 s −1 as x increased from 0.1 to 0.6. The lowest resistivity of 9.2 × 10 −3 Ω cm was acquired for the film with x = 0.2. The average transmittances in the visible region for all the films were beyond 83%. The bandgap of the (In1- x Al x )2 O3 films can be regulated in the range of 3.85–4.88 eV by changing Al concentrations from 0.1 to 0.6.